Study of Photocarriers Lifetime Distribution in a‐Si:H via Magneto‐photoconductivity and Magneto‐Photoluminescence. Issue 16 (29th May 2022) - McLaughlin, Ryan; Pan, Xin; Sun, Dali; Kwon, Ohyun; Vardeny, Zeev Valy
Abstract: Herein, the magneto‐photoluminescence (MPL) of localized photocarriers and magneto‐photoconductivity (MPC) of delocalized photocarriers in amorphous hydrogenated silicon (a‐Si:H) films and devices, respectively, are investigated. Both responses are caused by mixing of spin sublevels in the photogenerated electron–hole (e–h) pairs that alters their recombination and dissociation rates. The spin mixing occurs by a combination of hyperfine interaction (HFI) between spin ½ photocarriers and neighboring 29 Si and 1 H nuclei, and the Δ g mechanism which originates from a difference in the Landé g ‐factors of electrons and holes. The existing disorder in a‐Si:H films leads to dispersive field response that is described by a unique dispersive parameter α < 1, from which the e–h lifetime distribution, g (τ) is obtained. The mean e–h lifetime is found to be ≈12 ns for the high‐energy, relatively delocalized photocarriers generating the photocurrent, as compared to ≈200 ps for the lower energy, trapped e–h pairs which yield photoluminescence. The MPL( B ) and MPC( B ) responses in a‐Si:H subjected to prolonged illumination that causes Staebler–Wronski type degradation, and subsequent annealing are studied. The illumination‐induced photocarrier localization that enhances the HFI component is found, which dramatically decreases upon annealing; this method can assess optoelectronic device degradation. Abstract : The magneto‐photoluminescence (MPL) and magneto‐photoconductivity (MPC) in amorphous hydrogenated silicon (a‐Si:H) films and devices are investigated. The disorder in a‐Si:H films leads to dispersive field responses described by a dispersive parameter α < 1, from which the electron–hole lifetime distribution is obtained. Prolonged illumination increases photocarriers localization which enhances the hyperfine interaction; these effects are partially restored upon annealing.